E-Learning for Teacher Training in Tanzania - Baker, D; Bliss, A; Chung, R (2013)
Rural Tanzania is struggling to provide an adequate number of qualified teachers to keep up with increased primary and secondary school enrollment rates. Teachers enter classrooms with minimal teaching experience and education, sometimes having never studied the subject they are teaching. As a result of this under-qualification, teachers struggle in critical topics such as math, science, and English, exacerbating the trend of low academic performance. A lack of well-qualified teachers means the country is producing students whose education is cut short, as they are not passing national exams for graduation. This result is a great disappointment and an unacceptable outcome for students who represent years of investment and hope for the future. Primary and secondary school teachers must have sufficient knowledge and skills in the classroom. Teacher training will need to employ a variety of tools, among them education of and with Information and Communications Technologies (ICTs). This project has two components. First, it provides a landscape review of national and international policies and initiatives that affect education in Tanzania, clarifying how Asante Africa’s programs can best fit into the country’s established systems. Second, it identifies best practices for using e-learning ICTs to train teachers and improve the country’s education system. The report identifies four prospective e-learning models, and recommends that Asante Africa consider aspects of two: mobile learning and massive open online courses (MOOCs). Through our model evaluation, we found that these two models ranked best for Tanzania in effectiveness, cost, rural feasibility, scalability, and sustainability. Once a delivery method is in place and Asante Africa ensures technical support for the teachers utilizing the training materials, Asante Africa can strategize a plan for content and curriculum that leverages its Khan Academy videos. By implementing the recommended ICTs for learning and teacher training, Asante Africa will deliver increased access of quality training to teachers in the rural districts of Tanzania, improving the academic environment and performance of students throughout the country.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:learning; F:ministry; P:teacher training; Q:e-learning; Q:mobile learning; T:TVET; publicImportV1; ⛔ No DOI found